The Expression of Natural Phenomena Associated with Water and Fire in Poetry - Sh.Sh.Nizomova (Zien Journals, 2021)
This article discusses the interpretation of natural phenomena related to water and fire in modern poetry and its interpretation in Uzbek poetry
Keywords: Poetry; Ceremony; Family-Life Ceremony; Image